2007
DOI: 10.1002/adfm.200600938
|View full text |Cite
|
Sign up to set email alerts
|

Strain Accommodation during Phase Transformations in Olivine‐Based Cathodes as a Materials Selection Criterion for High‐Power Rechargeable Batteries

Abstract: High energy lithium‐ion batteries have improved performance in a wide variety of mobile electronic devices. A new goal in portable power is the achievement of safe and durable high‐power batteries for applications such as power tools and electric vehicles. Towards this end, olivine‐based positive electrodes are amongst the most important and technologically enabling materials. While certain lithium metal phosphate olivines have been shown to be promising, not all olivines demonstrate beneficial properties. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
426
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(456 citation statements)
references
References 33 publications
29
426
0
1
Order By: Relevance
“…In contrast, the overpotential is nearly constant and quite small at low current (C/2000−C/ 500), which is the energy needed for phase nucleation since this approaches the zero-current limit and thus thermodynamics dominates. 38 The inset in Figure 5B shows the low-current region. The overpotential approaches ∼20 mV at zero current.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast, the overpotential is nearly constant and quite small at low current (C/2000−C/ 500), which is the energy needed for phase nucleation since this approaches the zero-current limit and thus thermodynamics dominates. 38 The inset in Figure 5B shows the low-current region. The overpotential approaches ∼20 mV at zero current.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One good example of a collective variable for reorganizations in solids might be the lattice parameters that have also been often used to explain kinetics of cathode materials in the battery field (35). Because the cathode materials have a coherent or semicoherent interface between charged and discharged phases (36), the lattice parameters evolve gradually between those of the two phases, implying that the reaction pathway can be well defined along the changing lattice parameters.…”
Section: Significancementioning
confidence: 99%
“…The effect of the elastic strain energy on battery reactions has been discussed in some negative electrodes such as Sn-Li and Al-Li alloys, [6][7][8] and in a positive electrode, especially LiFePO 4 . [9][10][11] Cogswell et al 12 mentioned in the phase-field simulation that the large coherent strain energy in the LiFePO 4 /FePO 4 electrode suppresses the phase change during charge/discharge processes. In our recent papers, it has been demonstrated with the phase-field micromechanical simulation that the coherent strain suppresses nucleation process inside the material and significantly retards even in spinodal decomposition, 13 and also shown that the coherent strain strongly affects the spinodal decomposition of nanometer-sized particles.…”
mentioning
confidence: 99%